2016
DOI: 10.7314/apjcp.2016.17.s3.317
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of BUB1b Gene Expression in Sentinel Lymph Node Biopsies of Invasive Breast Cancer in Iranian Female Patients

Abstract: Detection of micrometastasis in sentinel lymph nodes (SLNs) is a very useful tool for appropriate assessment of the clinical stage of disease in breast cancer patients. Early identification of clinically relevant disease could lead to early treatment or staging approaches for breast cancer patient. Micrometastases in SLNs of women with invasive breast cancer are of great significance in this context. In this study we examined SLN biopsies considered to have small numbers of cancerous cells by real time RT-PCR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Our validation showed that the expression patterns of BUB1B, CCNB1, CDC20, COL10A1, CYCS, EEF1A2, gap junction protein beta 2 (GJB2), KPNA2, PTTG1, RAB31, TTK, UBE2C, ELF5 and STAC2 were the same in all individual patients. These genes have been reported as cancer-related for breast cancer [2325, 3745].…”
Section: Discussionmentioning
confidence: 99%
“…Our validation showed that the expression patterns of BUB1B, CCNB1, CDC20, COL10A1, CYCS, EEF1A2, gap junction protein beta 2 (GJB2), KPNA2, PTTG1, RAB31, TTK, UBE2C, ELF5 and STAC2 were the same in all individual patients. These genes have been reported as cancer-related for breast cancer [2325, 3745].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression or mutations of BUB1B can cause aneuploidy. Several studies have revealed that BUB1B overexpression is associated with the progression and recurrence of bladder cancer, 36 gastric cancer, 37 breast cancer, 38 , 39 prostate cancer, 40 and other malignancies. There is currently no clear evidence for the relationship between BUB1B and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of BUB1B in prostate cancer cells promotes cell proliferation and migration [ 16 ]. BUB1B was expressed higher in invading metastasized breast cancer cells than in those without metastasis [ 17 ]. BUB1B localizes to centrosomes, physically interacts with PLK1 and inhibits the phosphorylation and kinase activity of PLK1 during interphase [ 18 ].…”
Section: Discussionmentioning
confidence: 99%